New SAPIEN XT System is Noninferior to and Safer Than Old SAPIEN System - Vinall, Phil (MD Conference Express, 2013)
Results from the Placement of Aortic Transcatheter Valves 2 trial [PARTNER 2; NCT01314313] indicated that the new SAPIEN XT transcatheter heart valve system is noninferior to the old SAPIEN system when used in an inoperable cohort of patients. The new slimmer version was associated with improved procedural outcomes and reduced vascular complications, including major vascular bleeding.